Academic parenthood in the United Arab Emirates in the time of COVID-19 - Dickson, Martina; Midraj, Jessica; Al Hakmani, Rehab; McMinn, Melissa; Elsori, Deena; Alhashmi, Mariam; Tedam, Prospera (Frontiers in Education, 2023)
Since the onset of the global COVID-19 pandemic, early research already indicates that the personal and professional impact on academics juggling parenting responsibilities with their academic work has been immense. This study, set in the United Arab Emirates, explores the experiences of academic parents and looks at ways in which various aspects of their professional lives have been affected by the pandemic. Survey data from 93 participant parents indicated that certain elements of research productivity have been reduced during the pandemic, and having to support children with online schoolwork while teaching online themselves has been particularly stressful. Working from home with no dedicated space was a frequent challenge for the academic parents, and this impacted their ability to perform research tasks that demanded quiet spaces, e.g., reading and writing. However, the data also indicated that parents appreciated greater working flexibility, a reduction in commuting time, and being able to be more involved in their family lives. Some indications were perhaps unexpected, such as no statistically significant impact being observed on academic parents’ ability to interact with students or peers at their institutions while working from home. The implications of these findings to faculty and institutions are discussed.